Dermoscopic Features of Erosive Pustular Dermatosis of the Scalp: A Comparative Multicentric Retrospective Study in Bald and Hairy Patients - Plozner N; Zelin E; Zalaudek I; Lallas A; Piraccini BM; Starace M; Errichetti E (Clinical, Cosmetic and Investigational Dermatology)
Noemi Plozner,1 Enrico Zelin,1 Iris Zalaudek,2 Aimilios Lallas,3 Bianca Maria Piraccini,4,5 Michela Starace,4,5 Enzo Errichetti1 1Institute of Dermatology, Department of Medical Area, University of Udine, Udine, Italy; 2Department of Dermatology, ‘Maggiore’ Hospital, University of Trieste, Trieste, Italy; 3First Dermatology Department, School of Medicine, Faculty of Health Sciences, Aristotle University, Thessaloniki, GR-54124, Greece; 4Dermatology Unit, IRCCS Azienda Ospedaliero-Universitaria di Bologna, Bologna, Italy; 5Department of Medical and Surgical Sciences, University of Bologna, Bologna, ItalyCorrespondence: Noemi Plozner, Institute of Dermatology, Department of Medicine, University of Udine, Piazzale Santa Maria della Misericordia, 15, Udine, 33100, Italy, Tel +39 0432559822, Email noemiplozner@hotmail.itBackground: Erosive pustular dermatosis of the scalp (EPDS) is a rare inflammatory disorder primarily affecting elderly individuals with bald or hairy scalps. It is often misdiagnosed due to clinical overlap with other scalp conditions. Dermoscopy is an invaluable diagnostic tool for hair and scalp disorders, but its utility in EPDS remains underexplored. This study aims to identify dermoscopic features of EPDS and compare them with differential diagnoses to improve non-invasive recognition.Materials and Methods: A retrospective multicentric study was conducted across three Italian dermatological centers. Two cohorts, bald and hairy patients with histologically confirmed EPDS, were compared with controls diagnosed with conditions mimicking EPDS. Dermoscopic images at 10× magnification were analyzed by two independent evaluators using standardized criteria. Comparative analyses of dermoscopic features and interobserver agreement were performed, with statistical significance set at p< 0.01.Results: A total of 116 patients [53 bald patients (28 with EPDS and 25 controls) and 63 hairy patients (32 with EPDS and 31 controls)] were included in the study. Among EPDS bald patients, linear-curved vessels (unspecific distribution) (78.6%), orange structureless areas (diffuse) (46.4%), and yellow scales/crusts (focal) were the main findings, whereas focal yellow scales/crusts (84.4%) and the “peripheral horizontal hair” sign (84.4%) turned out to be the most common features in EPDS hairy patients. Comparative analysis revealed linear-curved vessels (p< 0.001), orange structureless areas (diffuse) (p< 0.001) and non-follicular pustules (p=0.005) to be distinctive features of EPDS in bald patients, while yellow scales/crusts (focal), non-follicular pustules and “peripheral horizontal hair” sign (horizontally arranged hair whose proximal part of the shaft is seen through a thinned epidermis at the edge of alopecic areas) were related (p< 0.001) to EPDS in hairy patients. Interobserver agreement was excellent (Kappa=0.81– 0.83).Conclusion: Dermoscopy provides valuable diagnostic clues for EPDS, distinguishing it from other scalp disorders.Keywords: alopecias, dermoscopy, diagnosis, differential diagnosis, hair disorders